The brain-compatible classroom : Using what we know about learning to improve teaching - Erlauer, Laura (Alexandria : Association for Supervision and Curriculum Development, 2003)
This book summarizes current brain research and shows how teachers can use this knowledge in the classroom every day. It explores how the brain works, how students' emotions and stress affect their ability to learn, how the physical classroom environment influences learning, and what forms of assessment work best. An introduction discusses the process of change toward brain compatible learning and provides an overview of the seven brain compatible functions. Nine chapters focus on: (1) "A Walk Through the Brain"; (2) "Emotional Wellness and a Safe Environment"; (3) "The Body, Movement, and the Brain"; (4) "Relevant Content and Student Choices"; (5) "Time, Time, and More Time"; (6) "Enrichment for the Brain"; (7) "Assessment and Feedback"; (8) "Collaboration"; and (9) "Leadership Strategies to Promote Brain-Compatible Learning." Each chapter provides examples from real classrooms, showing how the research can be used to improve student learning. The ideas and strategies presented are from a variety of grade levels and subject areas and can be used immediately to create a classroom where students can reach their full potential. (Contains 62 references.) (SM
Includes bibliography and index.
Keywords: Learning; Teaching